2012
DOI: 10.1016/j.jvs.2012.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional anesthesia for endovascular aneurysm repair

Abstract: The absence of randomized data is a major hurdle to understanding the effect of anesthetic technique on morbidity after EVAR. The data presented are encouraging in selected patients. The use of locoregional anesthesia for EVAR should be further investigated with better reporting of aneurysm morphology to clarify its potential benefits and identify the subgroups that will derive greatest benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 50 publications
2
29
1
8
Order By: Relevance
“…It was evident from early experience that it is possible to perform EVAR surgery under different types of anesthesia, including general (GA), regional (RA) and local anesthesia (LA) 12,13 . Non-randomized studies conducted 10 years ago, as well as a systematic review, suggested possible patient benefit when local and/or regional techniques are used for EVAR [14][15][16][17] . Recently, a post-hoc analysis of the Immediate Management of Patients with Rupture: Open Versus Endovascular Repair (IMPROVE) trial showed that patients who had emergency EVAR surgery for rAAA under LA had a significantly reduced odds of death in the 30-days following surgery compared to those who had GA 18 .…”
Section: Introductionmentioning
confidence: 99%
“…It was evident from early experience that it is possible to perform EVAR surgery under different types of anesthesia, including general (GA), regional (RA) and local anesthesia (LA) 12,13 . Non-randomized studies conducted 10 years ago, as well as a systematic review, suggested possible patient benefit when local and/or regional techniques are used for EVAR [14][15][16][17] . Recently, a post-hoc analysis of the Immediate Management of Patients with Rupture: Open Versus Endovascular Repair (IMPROVE) trial showed that patients who had emergency EVAR surgery for rAAA under LA had a significantly reduced odds of death in the 30-days following surgery compared to those who had GA 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The published studies have been observational in nature and are susceptible to selection bias. [30][31][32][33][34] A pooled analysis of 10 studies comparing the outcomes of local anesthesia (LA) and GA in 13,459 patients undergoing EVAR found no difference in the 30-day mortality between patients receiving LA and those receiving GA. 35 EVAR conducted under LA was associated with statistically shorter operative times and hospital lengths of stay. However, the sizes of these effects were clinically insignificant (< 1 min differences in pooled operating times and less than a half-day of pooled difference in hospital stay).…”
Section: Anesthetic Techniquementioning
confidence: 90%
“…The choice of anesthetic technique in these studies may be a reflection of the surgeon's experience or the surgical complexity of the aneurysm. 35 Thus, the choice of anesthesia should be based on local practice, the anticipated length of the procedure, and the preferences of the surgeon and the patient. The use of LA may be accompanied by light sedation.…”
Section: Anesthetic Techniquementioning
confidence: 99%
“…Percutaneous access directed by ultrasonography and usage of closure devices reduces the operation time and decreases the number of physicians required. [21] Local anesthesia has also an advantage to general anesthesia in terms of postoperative outcomes; and it also shortens the hospitalization time according to regional and general anesthesia. [21] However, EVAR cannot be performed in all patients due to access problems mainly caused by problematic iliac morphology.…”
Section: Discussionmentioning
confidence: 99%